Hindu Tales from the Sanskrit - D'Anvers, N., 1844-1933; Mitra, Siddha Mohana, 1856-1925 (Salt Lake City, UT : Project Gutenberg, 2004)
"Hindu Tales from the Sanskrit" by N. D'Anvers and Siddha Mohana Mitra is a collection of traditional stories drawing on the rich tapestry of Hindu mythology and folklore, dating back to the early 20th century. This anthology features narratives that captivate young readers while imparting moral lessons and cultural values deeply rooted in Hindu philosophy. Among the central characters introduced is Subha Datta, a woodcutter whose life changes dramatically when he encounters fairies and comes across a magical pitcher that can fulfill his desires. The opening of the book establishes the context with an introductory note outlining the significance of these tales in Hindu culture and their role in moral and personal development for children. It begins with "The Magic Pitcher," introducing Subha Datta as a loving father who, in pursuit of better resources for his family, becomes entangled with fairies who tempt him with promises of ease and abundance but lead him to internal conflict regarding his true responsibilities. As he grapples with his newfound life of luxury away from his family, the themes of temptation, responsibility, and the consequences of selfishness begin to unfold, setting the stage for the lessons he will ultimately need to confront. (This is an automatically generated summary.)
The magic pitcher -- The story of a cat, a mouse, a lizard and an owl -- A royal thief-catcher -- The magic shoes and staff -- The jewelled arrow -- The beetle and the silken thread -- A crow and his three friends -- A clever thief -- The hermit's daughter.
Release date is 2004-02-01
Keywords: Tales -- India; Sanskrit literature -- Translations into English